2017
DOI: 10.3847/1538-3881/aa8ad3
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Positioning of Interferometric Array Antennas Using Division Algorithm for Radio Astronomy Applications

Abstract: The Square Kilometre Array (SKA) ushers in the new generation of large radio telescopes that will work at wavelengths between meters and centimeters. In order to competitively design interferometric antenna arrays such as SKA, it is crucial to focus on the optimization of system performance. In this paper, we contribute to the solution by introducing a new optimization algorithm called Division Algorithm (DA). This algorithm finds the optimal positions of antennas to simultaneously maximize u-v coverage and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The DA has been simpler, more precise, faster, and more flexible than GA in solving problems. 27,58 In this paper, the DA has been developed to optimize the size of three SAHRES configurations by considering the constraints of the object function, such as the LPSL, A WT , A PV , and N BBS . Figure 5 demonstrates the implementation process of the division algorithm for this study.…”
Section: Division Algorithm (Da)mentioning
confidence: 99%
See 3 more Smart Citations
“…The DA has been simpler, more precise, faster, and more flexible than GA in solving problems. 27,58 In this paper, the DA has been developed to optimize the size of three SAHRES configurations by considering the constraints of the object function, such as the LPSL, A WT , A PV , and N BBS . Figure 5 demonstrates the implementation process of the division algorithm for this study.…”
Section: Division Algorithm (Da)mentioning
confidence: 99%
“…Division algorithm can also work without operators, such as crossover and mutation, to reduce the complexity. The DA has been simpler, more precise, faster, and more flexible than GA in solving problems 27,58 …”
Section: Optimization Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…In comparison (Boone, 2002), analyzed dense arrays and concluded that Gaussian radial‐distributions achieve a desired Gaussian beam. Numerous attempts at optimization of antenna placement have been reported (e.g., Boone, 2001; Cohanim et al., 2004; Cornwell, 1988; Gauci et al., 2013; Kogan, 2000; Kiehbadroudinezhad et al., 2017; Su et al., 2004). Consideration has also been given to how add to an existing array optimally (e.g., Karastergiou et al., 2006).…”
Section: Introductionmentioning
confidence: 99%